Study on Trap Barrier System Towards Rodent Population and Rice Production in Tidal-Area of South Sumatera Indonesia - Pujiastuti, Yulia; Sitompul, Kristian B.; Suparman, Suparman; Weni, Hastin WS; Herlinda, Siti; Hadi, Buyung A. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Rice cultivation in tidal area faces many obstacles. Rodent is one of important pests attacking rice both in vegetative and generative phases. The objectives of this research were to study the rat species and population, footprints, symptoms and level of rice damage and rice production by Trap Barrier System (TBS). The study was conducted in Jalur 6 of Muara Telang Banyuasin district, South Sumatera, 2016-2017. The research was carried out in two hectares of rice field with one hectare TBS and one-hectare non-TBS. Observation of rat population was done three times, during vegetative stage (30 days after planting/dap), reproductive stage (65 daps) and ripening stage (100 daps). One species of rats had been found namely Rattus argentiventer. In non-TBS, rat population was lower. However, in the damage level, the rat population was higher than in TBS. The number of R. argentiventer male captured was more extensive than the female. The number of footprints did not represent the number of rodents caught. The existence of rat footprints was indicating the existence of rat effort to approach the rice plant. The yield of rice was higher in TBS area.